Pembuktian Potensi Kerugian dalam Gugatan terhadap Keputusan Tata Usaha Negara - Rizky Ramadhan Baried (SASI, 2021)
Administrative court verdict number 04/G/2013/PTUN.YK. juncto 149/B/2013/PT.TUN.SBY., verdict number 18/G/2015/PTUN.YK. juncto 115/B/2016/PT.TUN.SBY. juncto 37 PK/TUN/2017, and verdict number 14/G/2017/PTUN.YK. juncto 205/B/2017/PT.TUN.SBY. were example that license (as the state administrative decision) issued by administrative officials as the object of lawsuit in administrative court, by the reason of potential loss, which normatively regulared by law number 9 of 2004 and its expansion in law number 30 of 2014. As known, principle of ‘negativa non sunt probanda’ state that facts that have not/not yet been proven cannot be proven, while it is opened by the regulation above, of course it will have implications for the procedure of evidence in court to arouse the confiction of judges and affordability of Article 53 of law number 9 of 2004 in a lawsuit with a potential loss reason. This research is an empirical legal research with statutory, conceptual, and case approaches. Subject of this research was administrative judges of Yogyakarta Administrative Court as primary data and analyzed qualitatively. The results showed that the judge could prove the potential loss as the basis of lawsuit by assessing the legal standing of plaintiff, whether plaintiff had an interest in the issuance of the state administrative decisions or not. Meanwhile, potential losses can be proven by means of a systematic interpretation between Article 53 of law number 9 of 2004 and Article 87 of law number 30 of 2014.